Plotino e o argumento do terceiro homem - Pitteloud, Luca (Voluntas: Revista Internacional de Filosofia, 2020)
This paper proposes to pose the question of a possible position of Plotinus with regard to the Argument of the Third Man (TMA): first, we will examine if it is possible to attribute to Plotinus a position as regards TMA such as it appears in the Parmenides, in particular with regard to the premise which affirms the self-predication (SP) of the Forms. Next, we will briefly consider how the question of the soul-body relationship can, to some extent, provide a better understanding of why Plotinus does not bother to give an explicit objection to TMA. Finally, we will analyze how the theory of two kinds of resemblance strikes a fatal blow to the spirit of TMA.